2020
DOI: 10.1002/dvdy.185
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific expression of ribosomal protein paralogue eRpL22‐like in Drosophila melanogaster eye development

Abstract: Background Differences in core or tissue‐specific ribosomal protein (Rp) composition within ribosomes contribute to ribosome heterogeneity and functional variability. Yet, the degree to which ribosome heterogeneity modulates development is unknown. The Drosophila melanogaster eRpL22 family contains structurally diverse paralogues, eRpL22 and eRpL22‐like. Unlike ubiquitously expressed eRpL22, eRpL22‐like expression is tissue‐specific, notably within the male germline and the eye. We investigated expression with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Although some dRPG are known, the best‐studied examples of metazoan dRPGs are those encoding RPL22/eL22. This eukaryote‐specific RP is encoded by two genes eL22 and eL22‐like, which are required for development in Drosophila (Gershman, Pritchard, Chaney, & Ware, 2020; Mageeney et al, 2018; Mageeney & Ware, 2019). Flies depleted of eL22 and rescued by eL22‐like overexpression have reduced fertility, confirming that eL22‐like cannot fully substitute for its paralog's function.…”
Section: Rpgs Structure Organization and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some dRPG are known, the best‐studied examples of metazoan dRPGs are those encoding RPL22/eL22. This eukaryote‐specific RP is encoded by two genes eL22 and eL22‐like, which are required for development in Drosophila (Gershman, Pritchard, Chaney, & Ware, 2020; Mageeney et al, 2018; Mageeney & Ware, 2019). Flies depleted of eL22 and rescued by eL22‐like overexpression have reduced fertility, confirming that eL22‐like cannot fully substitute for its paralog's function.…”
Section: Rpgs Structure Organization and Distributionmentioning
confidence: 99%
“…Profiling ribosomes carrying one or the other copy of eL22 by RNA‐seq identified 12,051 transcripts (mRNAs/noncoding RNAs), of which half were enriched in the ribosome incorporating one or the other paralog. Analysis of the mRNAs with modified translation suggested that the specific paralogs indeed influenced the translation of a specific set of genes associated with development, especially spermatogenesis (Gershman et al, 2020; Mageeney et al, 2018; Mageeney & Ware, 2019). eL22 is also duplicated in mammals; work in mice suggests that unlike in Drosophila , the deletion of one or the other paralog affects the mRNAs bound but does not induce a major change in translation and both could be incorporated into active ribosomes (O'Leary et al, 2013).…”
Section: Rpgs Structure Organization and Distributionmentioning
confidence: 99%
“…Our results regarding the selectivity of mRNA association by gNAC marked ribosomes from the oocyte hint at the existence of these ribosomes as specialized, directed to translation definite mRNAs, but this hypothesis requires in-depth study of ribosome proteins and RNA of these ribosomes. However, the topic of translation specificity realized by special ribosomes is actual (Gerst, 2018; Li and Wang, 2020; Gay et al, 2022), which is also associated with Drosophila ribosomes (Gershman et al, 2020; Jang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal proteins (Rps) are structural and noncatalytic components of ribosomes ( Lee et al, 2018 ), and Rps from the small and large subunits are named as RPS and RPL, respectively ( Kuang et al, 2020 ). All the core and tissue-specific RPS and RPL compositions within ribosomes could contribute to ribosome heterogeneity and functional variability ( Kronja et al, 2014 ; Gershman et al, 2020 ). Moreover, some studies have suggested that Rps are essential for reproduction and oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%